Simulasi Mesin Pencampur Kopi Otomatis dengan Metode Tunning PID pada LabVIEW - Ade Rustandi (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2016)
Abstract - Coffee is a drink that many people consume as an encouraging and casual meal. Coffee consumption can eliminate boredom due to daily activities. Therefore, coffee is very beneficial for people who enjoy coffee. But in serving doses of making coffee drinks in stalls or cafes still use manual methods, so the dose of coffee is not right. Every time you make a large amount of coffee drinks there may be several coffee drinks with different flavors. Therefore an automatic coffee maker is made so that the resulting coffee drink has the same taste. The system design for automatic coffee drink makers uses the LabVIEW application program, with the PID controller method to get the coffee content that you want to serve. The parameters of the content to be regulated are coffee, milk and sugar by setting the value of Kp = 398.52; Ki= 3.06; and Kd= 0.765. By setting a point, the value of the mixed content will remain stable as desired. Keyword : PID, Tunning PID, Coffe Mixer Simulation, LabVIEW, PID simulation, Coffe Mixer PID